2013
DOI: 10.1103/physreve.87.032206
|View full text |Cite
|
Sign up to set email alerts
|

Quasistatic rheology and microstructural description of sheared granular materials composed of platy particles

Abstract: This is the first paper of a series devoted to the micro-mechanical modeling of clayey soils, by means of discrete element simulations. We specifically focus here on the effect of the platy shape of particles by reducing the interactions between particles to mechanical contact forces (i.e., neither electrostatic repulsion nor van der Waals forces are taken into account). The particles are three-dimensional square plates, approximated as spheropolyhedra. Several samples composed of particles of different levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 37 publications
0
36
0
Order By: Relevance
“…Each interaction represents single or multiple contacts, each contact occurring between two elements belonging to either of the two spheroplates. All possible contacts are determined by considering two cases: a contact between two edges and a contact between a vertex and a face [40,31].…”
Section: Simulation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each interaction represents single or multiple contacts, each contact occurring between two elements belonging to either of the two spheroplates. All possible contacts are determined by considering two cases: a contact between two edges and a contact between a vertex and a face [40,31].…”
Section: Simulation Methodsmentioning
confidence: 99%
“…Our numerical setup is identical to that used for the investigation of shear strength and volume-change behavior in a previous paper by the same authors as a function of the degree of platyness of the particles [31]. The samples are composed of square plates, which we approximate as spheropolyhedra [29,8,30] and simulated by means of the Molecular Dynamics (MD) method.…”
Section: Introductionmentioning
confidence: 99%
“…The computational time is further reduced using a combination of the Verlet distance concept and neighbor tables that is tailored for this particular case of geometrical objects [43][44][45][46]. While the major application of this method has been the investigation of granular flow [47] and pedestrian flow [48], it is shown that particles generated by Minkowski sums are promising in the investigation of the effects of friction and rheology due in flat and nonconvex particles [49,50]. Here we exploit further the effect of nonconvexity on friction by using nonconvex spheropolygons with complex (fractal) topography.…”
Section: Spheropolygon-based Simulations Of Friction Between Fracmentioning
confidence: 99%
“…It is widely recognized that the internal structure of granular materials [1][2][3][4][5] has a significant influence on their macromechanical properties. Adopting reasonable parameters [6][7][8] and bridging the micro-and macrofields [9][10][11] have attracted a great deal of research in recent years [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Although many experiments are performed on the fabric of granular materials [7,15,16], which are complicated and expensive, the analysis is in dispute under some conditions. Initiated by Cundall and Strack [17], the discrete element 2 Mathematical Problems in Engineering method (DEM) for modeling the mechanical behavior of granular materials has been used to address many challenges in geotechnical engineering [5,[18][19][20]. The dispersibilities of the particle assemblies in granular materials give rise to some distinctive characteristics.…”
Section: Introductionmentioning
confidence: 99%